Tetrazole‐Substituted Five, Six, and Seven‐Membered Cyclic Amines Bearing Perfluoroalkyl Groups – Efficient Synthesis by Azido‐Ugi Reaction. Issue 28 (15th August 2013) - Shmatova, Olga I.; Nenajdenko, Valentine G.
Abstract: The application of perfluoroalkylated cyclic imines in azido‐Ugi reactions was studied. It was shown that the reaction allows access to five‐, six‐ and seven‐membered perfluoroalkylated cyclic amines connected to a tetrazole ring. The scope and limitations of this approach are discussed. When benzyl isocyanide was used in the azido‐Ugi reaction, it was shown that the tetrazole products could easily be debenzylated by catalytic hydrogenation to form 1 H ‐tetrazoles in excellent yields. Abstract : The application of perfluoroalkyl cyclic imines in azido‐Ugi reactions was demonstrated. The reaction was very general, and almost any 2‐substituted imines bearing CF3 or C2 F5 could be used to prepare tetrazole derivatives. When benzyl isocyanide was used in the azido‐Ugi reaction, the tetrazole products could easily be debenzylated by hydrogenolysis.